Reaching Pandemic Milestones with Country Primary and Secondary Vaccination Inflection Points: An Assessment of Foundational and Hybrid Fore (London Journal of Engineering Research, 2024)
The devastating worldwide impact of the COVID-19 pandemic created a need to better understand the effects of vaccination on case fatality rates (CFR) in a pandemic setting. Foundational time series forecasting models (ARIMA, Prophet, LSTM) and novel hybrid models (SARIMA-Bidirectional LSTM andSARIMA-Prophet-Bidirectional LSTM) were compared for performance and accuracy to forecast vaccination inflection points for 26 countries. Correlation analyses demonstrated that stringency index, age 65 and older, life expectancy, andpositive test rate, are factors correlating the most with the vaccination and case fatality rates. The primary vaccination inflection pointwas reached at 83.27 days (15-367 days), at the vaccination rate of 13.1% (0.1% - 50%), with 42% of countries seeing the initial impact in
Keywords: catalysis catalyst cabatier principle boudart principle; COVID-19; LSTM.; ARIMA; primary vaccination inflection point; secondary vaccination inflection point; Prophet; double hybrid; triple hybrid; SARIMA-Bidirectional LSTM; SARIMA-Prophet-Bidirectional LSTM